2006
DOI: 10.1186/1745-6215-7-34
|View full text |Cite
|
Sign up to set email alerts
|

Financial considerations in the conduct of multi-centre randomised controlled trials: evidence from a qualitative study

Abstract: Background: Securing and managing finances for multicentre randomised controlled trials is a highly complex activity which is rarely considered in the research literature. This paper describes the process of financial negotiation and the impact of financial considerations in four UK multicentre trials. These trials had met, or were on schedule to meet, recruitment targets agreed with their public-sector funders. The trials were considered within a larger study examining factors which might be associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, a recent systematic review showed that less than a third of the studied 114 randomized clinical trials achieved their planned sample size and that the recruitment period was extended for around half of the trials, usually supported by a supplementary grant, leading to less reliable results [ 37 ]. In a qualitative study related to the systematic review the authors state that "Securing and managing finances ... is a highly complex activity", "the ... system of dividing funds ... brought the trial teams into complicated negotiations with multiple funders", "The fact that all funders had the potential to influence and shape the trials ... was an important issue as the perspectives of applicants and funders could diverge", and "From development to completion ..., the trialists had to be resourceful and flexible, adapting to changing internal and external circumstances" [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review showed that less than a third of the studied 114 randomized clinical trials achieved their planned sample size and that the recruitment period was extended for around half of the trials, usually supported by a supplementary grant, leading to less reliable results [ 37 ]. In a qualitative study related to the systematic review the authors state that "Securing and managing finances ... is a highly complex activity", "the ... system of dividing funds ... brought the trial teams into complicated negotiations with multiple funders", "The fact that all funders had the potential to influence and shape the trials ... was an important issue as the perspectives of applicants and funders could diverge", and "From development to completion ..., the trialists had to be resourceful and flexible, adapting to changing internal and external circumstances" [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, large multicenter trials take a lot of time and effort to establish and can be expensive to run. 10 The required sample size needed to reliably demonstrate a clinically important effect should be based on the nominated primary endpoint of the study 11 ; this is sometimes lacking in anesthesia trials. 8,9 There may be several secondary study outcomes, and each of these typically relates to mechanisms of action, specific organ effects, and potential adverse effects of therapy.…”
mentioning
confidence: 99%
“…Other authors have documented the considerable time and other costs associated with involvement in trials [42][43][44], with some citing financial constraints as a significant barrier to involvement in (noncommercial) trials [37]. More than a decade ago Snowden et al [45] argued that financial considerations shaped all aspects of trial work and deserved far closer scrutiny than they had received. Our study helps to fill important gaps in understanding of the actual-and perceived-economics of trials research, and how these mould professionals' decisions and behaviours.…”
Section: Discussionmentioning
confidence: 99%